ANALISIS PENGUKURAN KINERJA PERUSAHAAN MENGGUNAKAN METODE BALANCE SCORECARD PADA PDAM KABUPATEN SUMENEP - Melly Husaima; Dessy Novitasari Laras Asih (Journal MISSY (Management and Business Strategy), 2026)
Rapid changes in the business environment mean that companies need Balanced Scorecard performance measurement, which covers all aspects. The aim of this research is to describe the performance of PDAM Sumenep using the Balance Scorecard. Type of quantitative descriptive research. The data used are financial reports, employee data, and customer data for PDAM Sumenep Regency for 2021-2023. Based on data management, the results of this study indicate the performance of four perspectives. From a financial perspective, performance declined, as seen from the NPM, ROA, and ROE values, due to a decrease in investment depreciation costs of IDR 5.4 billion. From a customer perspective, the MBR program successfully added customers, but satisfaction could be affected if service capacity is not increased. From an internal business process perspective, operational efficiency is maintained, but service expansion risks burdening the system without improving human resources and infrastructure. From a growth & learning perspective, employee retention is good, but productivity decreases due to an unbalanced workload.